3D-guided direct puncture therapeutic embolization of intracranial tumors. (1st March 2017) - Caroff, Jildaz; Benachour, Nidhal; Ikka, Léon; Nevoux, Jérôme; Parker, Fabrice; Da Ros, Valerio; Mihalea, Cristian; Iacobucci, Marta; Moret, Jacques; Spelle, Laurent
Abstract : Background: Direct punctures of intracranial tumors have rarely been described in the literature. Objective: To assess the feasibility, safety, efficacy, and advantages of using 3D DSA-guided direct puncture rather than the traditional transarterial route to preoperatively devascularize intracranial lesions in particular clinical situations, paying special attention to any correlation with surgical observations; we present the largest series to date. Methods: Between July 2015 and July 2016, data from all presurgical embolizations performed in our institution were prospectively collected. Information on tumor type, location, size, eventual bone erosion, complications, devascularization percentage, and estimated blood loss was analyzed. Results: Tumors of four patients (two meningioma, two endolymphatic sac tumor) were embolized using direct puncture. 3D XperGuide planning software was used in all procedures. Embolization was feasible in all cases. In one case, a small craniotomy was specifically performed to allow needle positioning. In all cases n-butyl cyanoacrylate was used. No ischemic or hemorrhagic complications related to embolization occurred. Complete or near complete devascularization was obtained in all cases. In one case, surgery was not performed and the patient was monitored. Resection was complete without significant blood loss in two cases, and resection was incomplete but satisfactory in one case. Conclusions: In selected cases, 3D-guided direct puncture of intracranial tumors appears safe, feasible, and efficient for preoperative embolization.